2006
DOI: 10.1161/01.atv.0000219289.06529.f1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Studies of Atherosclerosis

Abstract: Abstract-During the past 6 years, gene expression profiling of atherosclerosis has been used to identify genes and pathways relevant in vascular (patho)physiology. This review discusses some critical issues in the methodology, analysis, and interpretation of the data of gene expression studies that have made use of vascular specimens from animal models and humans. Analysis of gene expression studies has evolved toward the genome-wide expression profiling of large series of individual samples of well-characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…12 In addition to these mouse studies and single-gene approaches, a number of recent studies have assessed the role of transcriptome changes in the development of human atherosclerosis. 13 However, there is little direct knowledge about the in vivo role of the endothelium in the development of chronic atherosclerosis in humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition to these mouse studies and single-gene approaches, a number of recent studies have assessed the role of transcriptome changes in the development of human atherosclerosis. 13 However, there is little direct knowledge about the in vivo role of the endothelium in the development of chronic atherosclerosis in humans.…”
mentioning
confidence: 99%
“…13 One of the distinctive properties of human atherosclerosis is, however, the focality of its lesions, probably related to differences in local hemodynamics. 10,11 Hence, within a single artery, distinct regions with early or advanced plaques coexist with morphologically normal looking vascular wall, despite the fact that both individual genetic background as well as exposure to systemic, circulating risk factors such as high low-density lipoprotein (LDL) levels or proinflammatory cytokines are identical.…”
mentioning
confidence: 99%
“…It has been suggested that whole-genome measurements of complex traits like atherosclerosis should be performed on specific disease cell types separately (i.e., smooth muscle cells, foam cells, endothelial cells, and possibly T cells) in order to generate meaningful data (24). However, it is also quite possible-and in our view necessary-to view the plaque or lesion as a single functional system.…”
Section: Multiple-cell-type Versus Single-cell-type Diseasesmentioning
confidence: 99%
“…In published (24) and presumably in many unpublished or ongoing clinical trials, atherosclerotic plaques from patients undergoing carotid artery or coronary artery bypass grafting or specific atherosclerosis cell types obtained by LCM have been collected for whole-genome expression analysis to reveal genes central to atherosclerosis (21). Thus far, analyses of these datasets have been limited to traditional differential expression analysis and clustering.…”
Section: Gene Network Identification Of Atherosclerosis In Humansmentioning
confidence: 99%
“…Carotid and coronary arteries were most often used. 8 These analyses suggested that the differentially expressed genes were involved in inflammation, cell turnover, matrix degradation, lipid metabolism, coding for matrix proteins, or originated from smooth muscle cell proliferation or dedifferentiation.…”
mentioning
confidence: 99%